Relationship of Emotional Intelligence and Spiritual Intelligence Towards Educators Professionalism at SMP Negeri 34 Samarinda - Mahnunah, Siti; Toba, Rostanti (SYAMIL: Journal of Islamic Education, 2020)
This study aims to determine the relationship between emotional intelligence and spiritual intelligence towards the educators’ professionalism at SMP Negeri 34 Samarinda. This type of research is a field research with a quantitative approach, the data collection techniques in this study are observations and questionnaires which are then analyzed using the Alpha Cronbach formula, this is because the type of correlation in this study is multiple correlation, so to obtain valid and reliable results the calculation uses  the IMB SPSSP 20 with a significant level of 5%. The results found were the relationship between emotional intelligence and professionalism of educators at SMP Negeri 34 Samarinda was 0.750, and the relationship between spiritual intelligence and the professionalism of educators at SMP Negeri 34 Samarinda was 0.756, while the relationship between emotional intelligence and spiritual intelligence towards the professionalism of educators at SMP Negeri 34 Samarinda is 0.836. Thus all the existing variables are said to be related to one another.